PROFIL EVALUASI MODEL KIRKPATRIK PADA PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SYARIAH BAGI PENGURUS KOPERASI - ELOK NING FAIKOH (ACADEMIA: Jurnal Inovasi Riset Akademik, 2021)
This study aims to obtain an overview of the evaluation of the Kirkpatrik model level 1 and 2 in the implementation of the Sharia Financial Report Preparation Training for Cooperative Management. The research method used is descriptive quantitative. This study took a population of 30 participants of the Financial Report Preparation Training for Cooperative Management in Pasuruan Regency which was carried out by the East Java Province Cooperative and SME Training UPT. Level 1 evaluation (reaction) in this study was obtained by filling out a questionnaire with a Likert scale of 1 (one) to 5 (five) and level 2 evaluation (learning) was obtained by conducting pre-test at the beginning and post-test and at the end of the training. The results of the Kirkpatrik level 1 evaluation (reaction) describe the satisfaction (positive reaction) of the participants towards the implementation of the training. While the results of the level 2 evaluation (learning), there was an increase in knowledge about the material for preparing financial reports for cooperative management. An increase in post-test scores indicates an increase in the knowledge and skills of the trainees and is the success of the learning process ABSTRAKPenelitian ini bertujuan untuk mendapatkan gambaran tentang evaluasi model Kirkpatrik level 1 dan 2 pada pelaksanaan Pelatihan Penyusunan Laporan Keuangan Syariah bagi Pengurus Koperasi. Metode penelitian yang digunakan adalah deskriptif kuantitatif. Penelitian ini mengambil populasi peserta Pelatihan Penyusunan Laporan Keuangan bagi Pengurus Koperasi di Kabupaten Pasuruan yang di laksanakan oleh UPT Pelatihan Koperasi dan UKM Provinsi Jawa Timur sejumlah 30 orang. Evaluasi level 1 (reaksi) dalam penelitian ini didapat dengan melakukan pengisian kuisioner dengan skala Likert 1 (satu) sampai 5 (lima) dan evaluasi level 2 (pembelajaran) diperoleh dengan melakukan pre- test pada awal dan post- tes dan akhir pelatihan. Hasil evaluasi Kirkpatrik level 1 (reaksi) mengambarkan kepuasan (reaksi positif) dari peserta terhadap pelaksanaan pelatihan. Sedangkan hasil dari evaluasi level 2 (pembelajaran), terjadi peningkatan pengetahuan tentang materi penyusunan laporan keuangan bagi pengurus koperasi. Adanya peningkatan nilai post-test menunjukkan adanya peningkatan pengetahuan dan skill dari peserta pelatihan dan merupakan keberhasilan dari proses pembelajaran